Control of Turbulent Flow over a Circular Cylinder Using Tabs - Seo, Junyoung; Yun, Jinhyeok; Lee, Jungil (Mathematics, 2023)
In this study, we investigate tabs applied to turbulent flow over a circular cylinder for the reductions of the mean drag and lift fluctuations. Tabs are small and thin passive devices attached to the upper and lower surfaces of a circular cylinder near the flow separation. The Reynolds number considered is (Formula presented.) 3900, based on the free-stream velocity and cylinder diameter. Large eddy simulations are performed using a dynamic global subgrid-scale eddy-viscosity model. A parametric study is carried out to find the optimal tab configuration for minimizing the mean drag and lift fluctuations. Parameters considered are the height ((Formula presented.)) and width ((Formula presented.)) of the tabs, and spanwise spacing ((Formula presented.)) between them. With the optimal parameters, the spanwise coherence of the vortex shedding behind the cylinder is effectively disrupted, resulting in three-dimensional vortical structures varying in the spanwise direction. As a result, the strength of the vortex shedding in the wake is successfully weakened, and the mean drag and lift fluctuations are significantly reduced by 14% and 95%, respectively, with the optimal tab configuration of (Formula presented.), (Formula presented.), and (Formula presented.), where d is the cylinder diameter.
Keywords: drag; flow control; flow over a cylinder; lift; passive control; turbulent flow